Os custos da aterosclerose em Portugal - Costa, João (2021)
Introduction and objectives: Cardiovascular disease is the leading cause of death in Portugal and atherosclerosis is the most common underlying pathophysiological process. The aim of this study was to quantify the economic impact of atherosclerosis in Portugal by estimating disease‐related costs. Methods: Costs were estimated based on a prevalence approach and following a societal perspective. Three national epidemiological sources were used to estimate the prevalence of the main clinical manifestations of atherosclerosis. The annual costs of atherosclerosis included both direct costs (resource consumption) and indirect costs (impact on population productivity). These costs were estimated for 2016, based on data from the Hospital Morbidity Database, the health care database (SIARS) of the Regional Health Administration of Lisbon and Tagus Valley including real‐world data from primary care, the 2014 National Health Interview Survey, and expert opinion. Results: The total cost of atherosclerosis in 2016 reached 1.9 billion euros (58% and 42% of which was direct and indirect costs, respectively). Most of the direct costs were associated with primary care (55%), followed by hospital outpatient care (27%) and hospitalizations (18%). Indirect costs were mainly driven by early exit from the labor force (91%). Conclusions: Atherosclerosis has a major economic impact, being responsible for health expenditure equivalent to 1% of Portuguese gross domestic product and 11% of current health expenditure in 2016.